2017
DOI: 10.3390/su9122267
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Agricultural Ecosystem Services through the Integration of Perennial Polycultures into Crop Rotations

Abstract: This review analyzes the potential role and long-term effects of field perennial polycultures (mixtures) in agricultural systems, with the aim of reducing the trade-offs between provisioning and regulating ecosystem services. First, crop rotations are identified as a suitable tool for the assessment of the long-term effects of perennial polycultures on ecosystem services, which are not visible at the single-crop level. Second, the ability of perennial polycultures to support ecosystem services when used in cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 125 publications
(111 reference statements)
0
30
0
Order By: Relevance
“…In our study, however, WPMs are considered a promising option for biomass production on marginal agricultural land because they contain a mixture of on average five species (von Cossel & Lewandowski, ) and show features of a perennial system (Emmerling et al, ), for example, less soil disturbance and a well‐established rooting system. This promotes soil carbon accumulation, the development of soil biodiversity, and reduces the risk of erosion (Emmerling et al, ; Weißhuhn, Reckling, Stachow, & Wiggering, ). The costs of biomass production are also lower in perennial than in annual cropping systems (Lewandowski, ; Lewandowski et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, however, WPMs are considered a promising option for biomass production on marginal agricultural land because they contain a mixture of on average five species (von Cossel & Lewandowski, ) and show features of a perennial system (Emmerling et al, ), for example, less soil disturbance and a well‐established rooting system. This promotes soil carbon accumulation, the development of soil biodiversity, and reduces the risk of erosion (Emmerling et al, ; Weißhuhn, Reckling, Stachow, & Wiggering, ). The costs of biomass production are also lower in perennial than in annual cropping systems (Lewandowski, ; Lewandowski et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that they may be good practices to start with to perform an agroecological transition [50]. Additionally, as several authors previously assessed [60][61][62][63][64][65][66], most of the reviewed studies showed that both practices were highly positive in terms of carbon sequestration, climate regulation, erosion protection, pest control and pollination services, which could be an additional incentive for farmers to introduce these practices in their fields.…”
Section: Relationships Between Agroecological Practices and Ecosystemmentioning
confidence: 94%
“…Numerous papers have been published over the last decade describing predicted improvements in soil carbon balance, nutrient retention, soil water uptake efficiency, soil microbiome functions, and weed suppression, as annual crops that require soil disturbance and/or frequent exposure to maintain are replaced by perennial crops that require minimal soil disturbance or periods of exposure [1][2][3][4][5][6][7]. Other papers have addressed questions of why humans originally domesticated annual grain crops and what strategies make sense for domesticating new perennial grain crop species [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%